Friends, the television series : the official cookbook - Yee, Amanda (Insight Editions, 2020)
"Gather your friends and get ready to say, 'How you doin'?' to more than one hundred delectable and iconic recipes inspired by the hit sitcom Friends. " -- Page [4] of cover.